Fear of missing out and binge‐drinking among adolescents. (25th July 2021) - Brunborg, Geir S.; Skogen, Jens C.; Burdzovic Andreas, Jasmina
Abstract: Introduction: No previous studies have examined the cross‐sectional association between fear of missing out (FOMO) and binge‐drinking among adolescents. The aim of the present study was: (i) to estimate the magnitude of this association; (ii) to assess the impact of potential confounders (i.e. sensation‐seeking, symptoms of depression and self‐regulation); and (iii) determine if it is uniform across all levels of these characteristics. Methods: Cross‐sectional study of adolescents from 33 middle schools in Norway, stratified according to geographic location, urban and rural locations, and standard of living. Participants were a nation‐wide sample of N = 2646 adolescents (mean age 16.2 years, 43% boys). Self‐report data were collected on binge‐drinking, FOMO, sensation‐seeking, symptoms of depression and self‐regulation. Results: Overall, 21% reported binge‐drinking ≤ once per month in the past 12 months, while 9% reported binge‐drinking more than once per month. Multinomial logistic regression showed that the crude effect, where greater FOMO was associated with greater risk of binge‐drinking, was substantial (relative‐risk ratio = 1.50 [1.35, 1.66], P < 0.001), but somewhat attenuated after including all potential confounders (relative‐risk ratio = 1.28 [1.14, 1.43], P < 0.001). Effect modification analyses showed that the effect of FOMO on binge‐drinking ≤ once per month was stronger for adolescents with low symptom levels of depression and weaker for adolescents at high levels of depression. Discussion and Conclusion: Norwegian adolescents with higher FOMO have greater risk of binge‐drinking.